Estimation of Life Expectancy at Birth using Brass two Parameters Logit System from Sudan Census (2008) - Ahmed, Amer Abdoalwhab; Hamid, Mohamed Eldigire (Gezira Journal of Economic and Social Sciences; مجلد 7 عدد 1 (2016), 2016)
This study attempted to estimate the expectation of life at birth for males and females using Brass relational model from data of the fifth population census in Sudan (2008). The results of the study showed a remarkable difference in life expectancy at birth between males and females. Life expectancy at birth was calculated at (65years) for males and (70years) for females. The highest life expectancy at birth was calculated at (68.7years) for males in Gezira state and (71.8 years) for females in Northern state, while the lowest were found at (27.5years) and (36.2 years) for males and females respectively in West Darfur State. The results of the paired sample t test showed that the average life expectancy at birth for females was  calculated at (60years) compared with (56years) for males, which indicates that  the females in Sudan survived -on average- long time compared with males. The results of the paper strongly recommended using the mathematical Brass two Parameters logit model to smooth the data of mortality used in life table construction. Also, this model can be used to overcome the problems of distortion in similar models of nuptiality  and migration.